Gamelan Gender Wayang Composition “Sandaran Laju” | Komposisi Gamelan Gender Wayang “Sandaran Laju” - I Putu Purwangsa Nagara; I Nyoman Sudiana (GHURNITA: Jurnal Seni Karawitan, 2021)
Sandaran Laju is a musical artwork inspired by the interest in finding a different timbre from the Gender Wayang gamelan. Sandaran Laju musical form is an experimental piece of music, by making a pattern of the performance by attaching and playing two (2) instruments together so that a different new sound is created from the Gender Wayang gamelan. The meaning of the title Sandaran Laju is to “lean” or "rest" the aesthetic pattern of the existing tradition in Gender Wayang by offering a new processing and interpreting musical performances techniques, in order to create a different new sound from the Gender Wayang barungan. The composition structure of Sandaran Laju is divided into four (4) parts, in each part there are various systems, patterns, and motifs as the actualization of musical ideas from the composer. Sandaran Laju's experimental music is presented in the form of a video that had been through a previous recording process.